Calibration Procedure for Attenuation Coefficient Measurements in Highly Opaque Media Using Infrared Focal Plane Array (IRFPA) Spectroscopy. Issue 2 (February 2018) - Kirchner, Sara; Narinsamy, Sebastien; Sommier, Alain; Romano, Marta; Ryu, Meguya; Morikawa, Junko; Leng, Jacques; Batsale, Jean-Christophe; Pradère, Christophe
The purpose of this article is to present a new calibration procedure for spectroscopic measurements using an infrared focal plane array (IRFPA) spectrometer on highly opaque middle-wave infrared (MWIR) media. The procedure is based on the properties of the IRFPA camera and especially the integration time (IT), which is the main parameter that can be adjusted to control the sensitivity of the measurements. The goal of the paper is to experimentally validate this dependence with the direct reference intensity light coming out of the IR monochromator in order to predict the spectrum shape and intensity level in a range out of the camera saturation. This method allows determining spectrum used as background for transmittance calculation. It has been applied in the case of measurement of water transmittance, which is a highly opaque medium and whose measurement requires high ITs. The main result is the ability to take an IR spectroscopic imaging measurement through 300 µm of water and the determination of its transmittance with sufficient sensitivity due to the proposed calibration procedure. This procedure allows the possibility of transitory studies in heterogeneous aqueous media.